CÂMARA ESCURA: HISTÓRIAS E PRÁTICAS FOTOGRÁFICAS - Berno, Gládis; Oliveria, Stela M. Z. d.; Bigolin, Áurea; Lizot, Eleandro J.; Terra, Fernanda K.; Scortegagna, Paulo E. (Salão do Conhecimento, 2013)
Resumo